2020
DOI: 10.1158/1538-7445.am2020-ct302
|View full text |Cite
|
Sign up to set email alerts
|

Abstract CT302: Phase Ia/Ib dose-escalation study of the anti-TIGIT antibody tiragolumab as a single agent and in combination with atezolizumab in patients with advanced solid tumors

Abstract: Background: The immunomodulatory receptor TIGIT (T-cell Immunoreceptor with Ig and ITIM domains) is a novel inhibitory immune checkpoint present on activated T cells and NK cells in multiple cancers. In preclinical models, co-inhibition of the TIGIT and PD-L1/PD-1 pathways improved anti-tumor activity compared to either agent alone. Tiragolumab (tira or MTIG7192A) is a humanized IgG1/kappa monoclonal antibody (mAb) that binds TIGIT to prevent its interaction with its ligand PVR (CD155). In this first-in-human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Many of these combination therapies are showing success. For example, the PD-L1 inhibitor Atezolizumab plus Tiragolumab, an anti-TIGIT antibody (TIGIT is a highly expressed receptor both on T cells and NK cells) has shown early clinical activity with on ORR of 46% in patient with advanced solid tumors and is currently in phase I clinical trials ( 49 ). Many checkpoint inhibitor combinations have failed as well.…”
Section: Nk Cells and Immune Checkpoint Inhibitionmentioning
confidence: 99%
“…Many of these combination therapies are showing success. For example, the PD-L1 inhibitor Atezolizumab plus Tiragolumab, an anti-TIGIT antibody (TIGIT is a highly expressed receptor both on T cells and NK cells) has shown early clinical activity with on ORR of 46% in patient with advanced solid tumors and is currently in phase I clinical trials ( 49 ). Many checkpoint inhibitor combinations have failed as well.…”
Section: Nk Cells and Immune Checkpoint Inhibitionmentioning
confidence: 99%
“…Tiragolumab (MTIG7192A) showed good tolerability as both monotherapy and combinational therapy with atezolizumab, an anti-PD-L1 antibody, and preliminary but promising clinical activity in a phase I trial. In the trial, no response was observed from monotherapy, although the patients included were known to be resistant; however, out of 13 NSCLC patients receiving the combination, the response rate (RR) was 46% and diseasecontrol rate (DCR) was 85% (6). In a following randomized http://bmbreports.org BMB Reports phase II CITYSCAPE trial, an atezolizumab/tiragolumab combination compared with atezolizumab alone resulted in improved progression-free survival (PFS) with medians of 5.6 months versus 3.9 months, respectively, or 42% reduction in the risk of disease progression or death (stratified hazard ratio [HR], 0.58; 95% confidence interval [CI], 0.38-0.89).…”
Section: T Cell Immunoglobulin and Itim Domain (Tigit)mentioning
confidence: 99%
“…ORR was higher in patients receiving tiragolumab and atezolizumab (37.3% (CI 25–49.6) compared to those receiving placebo and atezoliumab (20.6% (CI 10.2–30.9), with an odds ratio of 2.57 (CI 1.07–6.14) ( 40 ). Tiragolumab with or without atezolizumab was also tested in patients with advanced solid tumors, in a Phase Ia/Ib dose escalation trial with TRAE of ≥ grade 3 in 4% of patients in each phase ( 41 ). There were three responses greater than stable disease in the Phase 1b portion, all of which occurred in PD-L1 positive patients.…”
Section: Alternative Checkpoint Receptor Pathwaysmentioning
confidence: 99%